INOVASI WAKAF PRODUKTIF SEBAGAI PILAR KEMANDIRIAN EKONOMI UMAT - Syauky, Ahmad; Mukhtari, Al (Yayasan An-Nur Meunara Baro, 2025)
Productive waqf is one of the key instruments in the Islamic economic system with great potential to achieve the economic independence of the Muslim community. This study aims to analyze the role of productive waqf innovation in building the pillars of Islamic economic empowerment through paradigm transformation, digital technology application, and the development of Sharia-based business models. Using a descriptive qualitative approach, data were collected from literature reviews, institutional reports, and previous related studies. The results show that technological innovation, such as Islamic financial technology (fintech) and digital waqf platforms, significantly enhances transparency, efficiency, and public participation in waqf management. Moreover, the integration of waqf with social investment and Islamic social enterprise provides new opportunities to generate sustainable economic value. Productive waqf serves not only as an act of worship but also as a fair wealth redistribution mechanism and a means of empowering the community’s economy. Therefore, the success of productive waqf management depends on professional governance, adaptive regulations, and strong collaboration among governments, Islamic financial institutions, and society. This study concludes that productive waqf holds strategic potential in realizing economic independence and collective welfare for the Muslim ummah in the modern era.